PENGARUH PERSEPSI LINGKUNGAN SEKOLAH TERHADAP PRESTASI BELAJAR PPKn SISWA SMA NEGERI PANDEGLANG BANTEN - E. Nita Prianti (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2018)
The Effect of School Environment Perception on the Achievement of Learning of PPKN Student of SMA Negeri 6 Pandeglang Banten. This research is conducted to take a purpose one of them is to know how far the influence of school environment perception (X1) to student's learning achievement (Y) so that the result obtained by one in learning and perceives according to capacity (ability, competence, and ability) it has. The method used in this research is the correlation method that is part of the type of quantitative research. Population in this research is student / student of class XI SMA Negeri 6 Pandeglang which amounted to 720 students. The sample in this research is 180 students taken by random sampling. The result of this research is the influence of school environment perceptions on the achievement of PPKN student of SMA Negeri 6 Pandeglang significantly. This is proved by the acquisition of tcount = 4.049 and Sig. 0,000 <0.05. Variable perception of school environment gives contribution of 30,10% to improvement of learning achievement of PPKN. Thus that there is influence of school environment perception to student achievement.